Hubungan Dukungan Keluarga dengan Sikap Ibu dalam Pemberian ASI pada Bayi Baru Lahir di RSIA Bunda Sejahtera Tangerang - Sianipar, Imelda M.G.; Sari, Sara Puspita; Doloksaribu, Juliyanti (Institut Kesehatan Immanuel, 2024)
Breastfeeding is the ideal food for babies that contains nutrition and complete antibodies. Breastfeeding in Indonesia is very low, at 30,2%. This percentage is still far below the WHO recommendation and the national target of 50%. Breastfeeding is influenced by the mother’s level of education and low family support. PP No. 33 of 2012 alsi states that family support plays an important role in efforts to indrease breastfeeding for infants. The purpose of the study was to determine the relationship between family support and mother’s attitude in breastfeeding babies at RSIA Bunda Sejahtera Tangerang. This research ia a descriptive quantitative type with a cross sectional approach. The number of respondents was 74 people, taken by using total sampling. Collecting data using analytical survey methods through questionnaires, documentation studies, and direct observation. The Kendall Tau test shows the Asymp value Sig. (2 sided) with p value = 0,000 < 0,05, so it can be stated that there is a significant relationship between family support and mother’s attitude in breastfeeding infants. The results of data analysis also showed that of the 74 respondents who received low support, 34 respondents (87.2%), while respondents who received high family support were found to have very good attitudes towards breastfeeding in the very good category, as many as 3 respondents (100 %). It means that when family give high support, the mother’s attitude is good, and when family support is low, the mother’s attitude is bad. The result of this study prove that family support is very important for the mother in breastfeeding their babies